JOGJA KOTA MURAL - Bambang Witjaksono M.Sn. (Ars: Jurnal Seni Rupa dan Desain, 2006)
Outline o f this research is to know the relation between art and power, m this case mural as anartwork and Yogyakarta municipality as the power holder. The power holder has the task to create a policyconcerning public space, including art in public space, and the function o f mural as one o f the specificcharacters o f Yogyakarta city.Besides it is also to know the program o f Yogyakarta municipality in managing its area, especiallythat which concerns art in public space, its relation with the aspects o f tourism, education and community'sinvolvement in designing the management o f public space in Yogyakarta city.Key ivords: Mural, Yogyakarta, Public space